2008
DOI: 10.1214/08-aoas167
|View full text |Cite
|
Sign up to set email alerts
|

Inference using shape-restricted regression splines

Abstract: Regression splines are smooth, flexible, and parsimonious nonparametric function estimators. They are known to be sensitive to knot number and placement, but if assumptions such as monotonicity or convexity may be imposed on the regression function, the shape-restricted regression splines are robust to knot choices. Monotone regression splines were introduced by Ramsay [Statist. Sci. 3 (1998) 425--461], but were limited to quadratic and lower order. In this paper an algorithm for the cubic monotone case is pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
173
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(175 citation statements)
references
References 15 publications
2
173
0
Order By: Relevance
“…See Meyer (2008) for a discussion of monotone splines. 28 Using those curves, the splines, the estimated elasticities are also increasing with higher mean consumption which is consistent with the arguments made by Ravallion and Chen (2011).…”
Section: Weakly Relative Poverty Versus Shared Prosperitymentioning
confidence: 99%
“…See Meyer (2008) for a discussion of monotone splines. 28 Using those curves, the splines, the estimated elasticities are also increasing with higher mean consumption which is consistent with the arguments made by Ravallion and Chen (2011).…”
Section: Weakly Relative Poverty Versus Shared Prosperitymentioning
confidence: 99%
“…It can be also derived from Meyer (2008) that at each knot exactly one basis function has a positive second derivative, so that for our convex splines the proper set of basis functions is up to order four. In the same work, it is also shown that for the unrestricted case and bounded mesh ratio the asymptotically optimal number of knots is l ≈ n 1/(2p+1) with p being the order of the polynomial pieces.…”
Section: Regression-based Estimation Via Shape-restricted Spline Regrmentioning
confidence: 99%
“…For our simulation purposes we used the code provided by Meyer (2008) in the supplementary material. As this estimate returns convex and monotone result, only the boundary condition is not necessarily satisfied.…”
Section: Regression-based Estimation Via Shape-restricted Spline Regrmentioning
confidence: 99%
“…Several authors have dealt with related problems using the isotonic regression for monotone regression models or for alternative shape constraints. Some representative references are Brunk (1970), Dykstra (1983), Hastie and Tibshirani (1986), Bachetti (1989), Huang (2002), Andersson et al (2004), Meyer (2008), Shively et al (2011) and Rueda and Lombardía (2012) among many others. There has been also considerable previous work on procedures testing homogeneity against monotonicity or unimodality (see for example Basso and Salmaso, 2011, Shi, 1988and Wolfe, 2006, but the problem of considering testing monotonicity against unimodality has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%